Skin Tightening Technologies - Greene, Ryan M.; Green, Jeremy B. (Facial Plastic Surgery, 2014)
Radiofrequency (RF) and intense focused ultrasound (IFUS) are increasingly used to address skin laxity of the face and neck. Both nonablative RF and ultrasound create a heat-induced tissue response that leads to collagen remodeling and other ultrastructural changes. Although these treatments are not meant to replace surgical procedures, patient satisfaction in the majority of studies has been consistently high. This article discusses the various RF and IFUS technologies currently in use and reviews pertinent clinical studies evaluating their efficacy and safety.
Keywords: radiofrequency; ultrasound; skin tightening; laxity